2004
DOI: 10.1136/bjo.2003.026385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mydriasis and different field strategies on digital image screening of diabetic eye disease

Abstract: Aims: To assess the effects of (1) mydriasis and (2) single versus three field photography on screening for diabetic eye disease using digital photography Method: Slit lamp examination findings were compared to digital fundal photographs for the detection of any retinopathy and for referable retinopathy in 398 patients (794 eyes). A Topcon TRC-NW6S digital non-mydriatic fundus camera was used. Three photographic strategies were used: undilated single field, dilated single field, and dilated multiple fields. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 28 publications
(17 reference statements)
4
102
1
5
Order By: Relevance
“…We are also pleased to report that the visual outcomes were satisfactory, possibly due to the prompt presentations and timely treatments, thereby ensuring that minimal harm was done by the screening process in line with World Health Organisation standards. 5 Murgatroyd et al 6 have shown that mydriasis with tropicamide improves the screening process by reducing the number of ungradable photographs from 26 to 5% in retinopathy screening.…”
Section: Discussionmentioning
confidence: 99%
“…We are also pleased to report that the visual outcomes were satisfactory, possibly due to the prompt presentations and timely treatments, thereby ensuring that minimal harm was done by the screening process in line with World Health Organisation standards. 5 Murgatroyd et al 6 have shown that mydriasis with tropicamide improves the screening process by reducing the number of ungradable photographs from 26 to 5% in retinopathy screening.…”
Section: Discussionmentioning
confidence: 99%
“…El programa ha tenido un impacto claro, aunque no cuantificado en este artí-culo, en la reducción del número de complicaciones de la retinopatía diabética atendidas en nuestras urgencias y en el número de vitrectomias realizadas en nuestro hospital secundarias a esta patología. Los porcentajes de retinografías sin midriasis, no valorables, oscilan entre el 9% y el 26% (23,24,25). Este porcentaje de exploraciones no útiles se reduce del 1,4% al 8% cuando se realiza con retinógra-fos de 45º en midriasis farmacológica (25,26).…”
Section: Tabla III Número De Revisiones Realizadas Y Número Medio Deunclassified
“…Los porcentajes de retinografías sin midriasis, no valorables, oscilan entre el 9% y el 26% (23,24,25). Este porcentaje de exploraciones no útiles se reduce del 1,4% al 8% cuando se realiza con retinógra-fos de 45º en midriasis farmacológica (25,26). Estos enfermos no valorables necesitan un examen posterior por un oftalmólogo.…”
Section: Tabla III Número De Revisiones Realizadas Y Número Medio Deunclassified
“…Nevertheless, photographic screening with centralised reading centres is rapidly becoming the most popular screening modality in the UK. 12 …”
Section: Screeningmentioning
confidence: 99%